OSTEOINDUCTIVE FACTORS FOR TREATMENT OF LONG-BONE NONUNION FRACTURES IN DOGS AND CATS - R. Vasileva (Bulgarian Journal of Veterinary Medicine)
Bone nonunion is defined as the body’s inability to heal a fracture. It is a serious complication that may occur when fracture instability, impaired blood supply or infection are present. Atrophic nonun-ion, that is radiographically displayed as absent callus, is the most common type of nonunion fracture. Its treatment still represents a great challenge in orthopaedics. Recent strategies focus on the use of growth factors with osteoinductive potential to induce osteogenesis and promote new bone formation. Therefore the aim of this review was to present and summarise currently available osteoinductive factors used to stimulate bone healing in cases of atrophic nonunion in dogs and cats; specifically recombinant human bone morphogenetic proteins (rhBMP), platelet-rich plasma (PRP), recombinant human erythropoietin (rhEpo), and recombinant parathyroid hormone (rPTH).